Um entendimento sobre o espaço vazio no contexto urbano - As Fontaínhas como laboratório urbano - Cláudia Raquel Bessa e Meneses Serra (2016)
The present Dissertation is in between project and theory, it aims to answerthe questions associated to the development of a urban project and temporaryresidence for Fontainhas in Porto, proposed in the fall semester 2014/2015 of"Advanced Studies in Architectural Design" - EAPA, at the Faculty of Architectureat the University of Porto. This course was completed with other subjects inparallel with Project and Construction, such as: History of Architecture; Theory ofContemporary Architecture; Urbanism; Design; Photography of Architecture; andCinema and Architecture. In this way, our theoretical approach was transversal tothe knowledge that involves Architecture practice.The structure of the Dissertation is in parallel with the development of theurban project and temporary residence. The project work was divided in threescales. The first works the relationship between the project field and the city,designing the overall organization - Urban Analysis. The second aims to designthe urban fabric and public space of Fontaínhas - Urban Project. In the end,we develop a temporary residence from it's shape in the city to the constructiondetails - Temporary residence. In this way, there were many doubts born fromthe development of this urban project and temporary residence that we intend toanswer in the present Dissertation:First of all, before the design of the urban project: What's the relationshipbetween Architecture and City? How can we relate the subjects of Architectureand Urbanism? How can we assume a urban project?Second, associated to the first phase of the project: How did urbanism begin?How was the urban planning implemented in Porto? How did the notion ofpublic space changed over time?Then, we arrived to the project field and its design: What's the meaningof "terrain vague" in the interpretation of the project field? What are the newmeanings of public space? How can we reinterpret architecture in the constructionof contemporary cities?In the end, associated to the design of the residence: What is typology inarchitecture? How can the residence typology draw the city form? How is drawnthe relationship between the individual house and the city, in the contemporarycity and society?In short, this is a line of thinking that goes from understanding the city andthe individual, passing by the architecture of public space and habitation.